THE GENUS VIBURNUM (CAPRIFOLIACEAE) IN MALAYSIA - J. H. KERN (Reinwardtia, 1951)
1. In the following pages an account of the genus Viburnum in Malaysia is presented. 2. The distribution of its species is briefly discussed and a map relating to it added. 3. The main part of the present paper consists of keys to the sections and species, followed by a systematic treatment of the 16 species admitted for the region. 4. Three new subsections are proposed, viz. Viburnum subsect. Punctata Kern,subsect. Sambucina Kern, and subsect. Lutescentia Kern. Viburnum subseries Coriacea Maxim, is reduced to the rank of a subsection. 5. Three species and two varieties are described as new, viz. Viburnum amplificatum Kern, V. clemensae Kern, V. hispidulum Kern, V. coriaceum, var. longiflorutn Kern, and V. sambucinum var. subglabrum Kern. 6. The following species are reduced to the rank of varieties: Viburnum floribundum Merr. has become V. luzonicum var. floribundum (Merr.) Kern, and V. sinuatum Merr. has become V. luzonicum var. sinuatum (Merr.) Kern. 7. The following reductions'to synonymy are made: Viburnum longistamineum Ridl. to V. sambucinum- var. subglabrum Kern; V. sumatranum Miq., V.villosum Ridl., and V. inopinatum Craib all to V. sambucinum var. tovientosum Hallier f.;V. forbesii Fawc. partly to V. sambucimim Bl., partly to V. coriaceum BL; and V. zippelii Miq. to V. japonicum (Thunb.) Spr. 8. Emended descriptions of Viburnum beccarii Gamble and of V. junghuhnii Miq. are given.